1881 Ark. Acts 191-92 - (:unkn) unknown (My University, 1881)
ch. 96, §§ 1-2: Prohibited the carrying of any dirk, Bowie knife, sword, spear cane, metal knuckles, razor, or any pistol (except pistols that are used in the Army or Navy if carried openly in the hand).
Keywords: CARRY